Market Segmentation and Product Positioning in Competitive Markets - Abdukhalilova Laylo Tokhtasinovna (Scientific Trends, 2025)
Market segmentation and product positioning are essential strategies for businesses to enhance their competitiveness, maximize customer satisfaction, and optimize resource allocation. This paper explores the theoretical foundations, methodologies, and practical implications of these strategies. The study employs a mixed-method approach, incorporating quantitative analysis of market segmentation criteria and qualitative insights from case studies. The findings reveal that effective segmentation and positioning lead to higher brand equity, improved customer loyalty, and increased profitability. The paper concludes with recommendations for firms to integrate advanced analytics and artificial intelligence (AI) for more precise segmentation and positioning strategies.
Keywords: Market segmentation, product positioning, competitive strategy, customer satisfaction, brand equity.